Potential of floating photovoltaic technology in Pakistan. (February 2021) - Muhammad, Abid; Muhammad, Umer; Abid, Zaineb
Abstract: Energy deficiency in different parts of the world is not only adversely affecting the quality of life of individuals but is also compromising the overall development of these areas. Pakistan is one of the energy-deficient countries of the world having high energy demand but less energy production, resulting in a consequent energy deficit of 2500 MW (Mega-Watt). Considering which, the current environmental and energy profile of Pakistan highlights the need for the country to shift to renewable energy sources to increase the production of clean energy. The availability of sufficient water bodies and suitable climate and terrain throughout the year makes Pakistan an extremely favorable region for the implementation of FPV (Floating Photovoltaic) technology to meet its energy demands. The current study proposes the prospects of implementing FPV technology in Pakistan. Also, it presents detailed discussion on environmental, economic, and technical aspects of FPV technology justifying its potential for Pakistan and other countries with similar regional profiles to adapt to the said technology.